2007
DOI: 10.1038/sj.mt.6300103
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Clonal Dominance in Cultured Human Lymphoid Cells by Addition of the cHS4 Insulator to a Lentiviral Vector

Abstract: Lentiviral vectors efficiently transduce quiescent stem cells and are being evaluated for gene therapy of blood dis-orders. The risk of genotoxicity as a result of insertional mutagenesis is an important safety consideration. The hy-persensitive site 4 insulator from the chicken beta-globin locus (cHS4) possesses chromatin bar-rier and enhancer-blocking functions. A control lentiviral vector encoding green fluorescent protein was compared with a vector in which the cHS4 insulator element flanked the green fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 44 publications
(60 reference statements)
1
49
0
Order By: Relevance
“…In our cell-based immortalization assay, we recently obtained evidence for a reduced genotoxic potential of g-retroviral and lentiviral vectors with more physiological cellular promoters (and Modlich U, unpublished data). The present study thus supports the emerging concept 17,19,54 that the type of the vector backbone and the nature of its cis-regulatory sequences are crucial variables to improve the therapeutic index of integrating vectors. The use of retroviral vectors containing strong, uninsulated enhancers should rather be restricted for the discovery of cancer-initiating genes in model systems (as shown here for Evi1 and Prdm16), or to clinical situations that offer no alternative.…”
Section: Perspectives For Gene Therapysupporting
confidence: 68%
“…In our cell-based immortalization assay, we recently obtained evidence for a reduced genotoxic potential of g-retroviral and lentiviral vectors with more physiological cellular promoters (and Modlich U, unpublished data). The present study thus supports the emerging concept 17,19,54 that the type of the vector backbone and the nature of its cis-regulatory sequences are crucial variables to improve the therapeutic index of integrating vectors. The use of retroviral vectors containing strong, uninsulated enhancers should rather be restricted for the discovery of cancer-initiating genes in model systems (as shown here for Evi1 and Prdm16), or to clinical situations that offer no alternative.…”
Section: Perspectives For Gene Therapysupporting
confidence: 68%
“…Here, our results introduce novel insulator elements suitable for implementation in viral vectors, endorsing previous reports on insulator elements able to reduce insertional genotoxicity. 9,26,44,45 The barrier activity of the novel insulating elements was probed in the context of random transgene chromosomal integration upon stable transfection. Flanking the transgene with CTCF binding sites led to a decrease in its expression, stably propagated over cell division.…”
Section: Discussionmentioning
confidence: 99%
“…New cellular 140 and animal 13 models have been developed to study genotoxicity potential of integrative vectors. Using these models, several groups have demonstrated the increase in safety of SIN vectors 12,141 and better performance of lentiviral over murine leukemia-based vectors. 13 In addition, although it was largely hypothesized that regulated expression should also reduce genotoxicity, Baum's group 113 recently demonstrated that tissue-specific and physiologically regulated vectors are indeed safer with no detectable transforming potential.…”
Section: Discussionmentioning
confidence: 99%